The Effect of Training to the Screening of Tuberculosis Suspected Children by Health Centers Officer - Rizka ‘Aﬁfatussalamah; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2014)
Children are one of the vulnerable groups to contract tuberculosis (TB), but so far, tuberculosis in children has not been a priority. The proportion of tuberculosis in children case finding is still low among all tuberculosis cases. Bojonegoro District is one of the districts in East Java designated as the operational trial of the tuberculin test. The case-finding begins with screening for suspected tuberculosis in children which determines how large the case of tuberculosis is found by officers at the Public health center (PHC). Health workers in health care facilities are the most dominant factor in the screening of suspected tuberculosis in children. Training on tuberculosis in children has only been conducted in 16 among 36 PHC in Bojonegoro District. This study aims to analyze the effect of training on the screening of suspected tuberculosis children by PHC officers in Bojonegoro District. This research is an observational analytic study with a cross-sectional design. The sampling technique is simple random sampling. The respondents consisted of 29 doctors and 29 midwives/nurses in 29 PHC of Bojonegoro District. The variables studied were training and screening for suspected tuberculosis children. The results of the study showed that most children with tuberculosis suspects were still lacking (75.9%) and officers who had never attended training on tuberculosis in children were 58.6%. Logistic regression test showed that there was an influence between training on the screening of suspected tuberculosis children (p = 0.019) and the prevalence rate showed that staff who had attended the training could screen children with suspected tuberculosis well by 8.50 times greater. Training about tuberculosis in children is needed, so that screening for suspected tuberculosis can be carried out more optimally.